1 The Colonial Laws of New York from the Year 1664 to the Revolution 231-32 (1896) - (:unkn) unknown (My University, 1691)
Lowered the minimum militia age, so that "noe person whatsoever from fiftieen to Sixty years of Age remaine unlisted." For every foot soldier, "a well fixed muskett or fuzee" for officers, "a good pike or Sword or lance and pistoll." At home, every foot soldier was to have "one pound of good powder and three pound of Sizeable bulletts," and every Trooper (horseman) had to "have at his usuall place of abode a well fixed Carabine with belt and Swivell and two pounds of fine powder with Six pounds of Sizeable bulletts."
Keywords: MILITIAS